Exploring Lecturers' Types of Feedback and Emotional Experiences in Giving Feedback on Students' Writing - Ibtiyanti, Maghfirotul Lailiyah Refania (Universitas Negeri Surabaya, 2022)
Giving feedback is an essential way to assist the students’ writing process. Therefore, the role of lecturers is entailed to help the development of students’ writing. In the process of giving feedback, the lecturer may experience some emotions including positive and negative emotions. A qualitative study was conducted in this research involving two English lecturers as the research participants. They were interviewed using a semi-structured interview. The purpose of this research was to reveal the types of feedback that were usually used by the lecturers and explore how the lecturers maintained their emotions during the process of providing feedback. The result of this research showed that the lecturers often used oral feedback for all students in a class to save more time. Related to the emotional experiences, it was found that both lecturers could give comprehensive feedback when they were in positive emotions, and vice versa.